Digital Interventions to Increase Financial Knowledge: Evidence from a Pilot RCT - Luis Oberrauch; Tim Kaiser (Institute of Labor Economics (IZA), 2024)
We study the effects of low-intensity digital financial education interventions on undergraduate students' financial knowledge in a small-scale RCT. We test the substitutability or complementarity of two treatments: an online video financial education treatment and an incentive-based approach where students are issued pre-paid voucher cards worth 50 EUR to register with a broker specializing in roboadvised investment in Exchange Traded Funds (ETFs). Three months after the intervention, the video treatment enhanced financial knowledge scores by more than 50 percent of a standard deviation. Conversely, the vouchers showed no effect. The findings suggest that subsidies encouraging roboadvised investment into ETFs cannot substitute direct financial education in our setting, and there is no evidence for complementarity between these interventions in creating human capital in the domain of financial decision-making.
Keywords: G53; 330; digital intervention; financial literacy; financial knowledge; financial education; robo-advisor; ETFs